Šolska knjižnica v devetletni osnovni šoli ter medpredmetno povezovanje: primer povezave knjižničnih informacijskih znanj in slovenščine v 9. razredu - Bizjak, Breda (Revija za elementarno izobraževanje, 2010)
School libraries in the nine-year compulsory primary school and cross- curricular cooperation : library and information expertise and Slovene language in class 9. The article presents the goals and tasks of a school library, information literacy and library science. A school library does not merely compliment learning in the classroom, it goes well beyond this: it enables pupils to study and learn on their own, without coercion. The librarian is not simply a lender of materials, but also an educator who fully participates in the educational process. Teaching supported by library and information expertise must be well organized. Good cooperation between the librarian and the teacher is a necessary condition for success. The library encourages pupils to study and make full use of all types of libraries independently. Here the reader will find a practical example of the connection between library science and the goals of the curriculum in Slovene language, which is made possible by the acquisition of knowledge via cross curricular teaching. Emphasis was put on the searching for information about available sources as it relates to a desired topic. Searching in a cross-departmental database is better through use of key words.